Hemodynamic effects of intraocular epinephrine during cataract surgery: a double blinded placebo controlled randomized clinical trial - Miratashi, Seyed Ali Mohammad; Behdad, Shekoufeh; Ayatollahi, Vida; Ahmadi, Afsar (Nepalese Journal of Ophthalmology, 2012)
Objective: To evaluate hemodynamic effects of intraocular epinephrine irrigation in patients undergoing cataract surgery. Materials and methods: This study was conducted as a prospective double blinded clinical trial at the Shahid Sadoughi University of Medical Sciences, Yazd, Iran. Eighty-eight patients of age 38-90 years undergoing were randomly allocated into two groups: Group E received intraocular irrigation fluid (balanced salt solution) with epinephrine 1:1000, 000, and group C received intraocular irrigation fluid (balanced salt solution) without epinephrine. Heart rate (HR), systolic and diastolic blood pressure (SBP, DBP) were measured before and at 5, 10, 15 minutes after starting intraocular infusion of epinephrine1:1000, 000 in both groups. Results: HR and SBP were similar in the two groups at different time intervals. DBP was decreased at 5 minutes after epinephrine administration in the epinephrine group and increased at 10 and 15 minutes but there was no significant differences between the two groups.Conclusion: Intraocular infusion of epinephrine 1:1,000,000 can be used during cataract surgery without hemodynamic side effects and so is a safe and effective method for this purpose.DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6546 Nepal J Ophthalmol 2012; 4 (2): 288-294